Test method for the aging process of pressure sensitive adhesives

By measuring the gelatin scoring rate of pressure -sensitive glue, it is determined that its mature state is determined, and the problem of high test costs in the process of allergic gum in existing technology has been solved, and the complete maturity of PSA glue and non -residual glue effect on PSA glue.

CN115236262BActive Publication Date: 2025-01-24TCL CHINA STAR OPTOELECTRONICS TECHNOLOGY CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202210907185.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-07-29
Publication Date
2025-01-24
Estimated Expiration
2042-07-29

AI Technical Summary

Technical Problem

The testing cost of the existing pressure-sensitive adhesive is high, resulting in the incompletely mature PSA adhesive that may overflow and adhere to the polarizer, causing residual glue problems.

Method used

By obtaining the gel score rate of pressure -sensitive glue after different time interval, it is determined whether PSA glue is cooked. When the gel scores obtained at least twice are within the preset deviation range, it is determined that PSA glue maturity is determined.

Benefits of technology

This method simplifies the testing of the pressure-sensitive adhesive curing process, reduces costs, ensures complete curing of the PSA adhesive, and avoids the problem of residual glue on the polarizer.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115236262B_ABST
    Figure CN115236262B_ABST
Patent Text Reader

Abstract

The present application discloses a method for testing the aging process of a pressure-sensitive adhesive, the method comprising the following steps: continuously obtaining the gel fraction of the pressure-sensitive adhesive at different time intervals; judging whether the pressure-sensitive adhesive layer is aging according to the gel fraction; and determining that the pressure-sensitive adhesive layer is aging when the gel fraction obtained at least twice in a row is within a preset deviation range. The method for testing the aging process of a pressure-sensitive adhesive of the present application can solve the problem of high cost of testing the aging process of the existing pressure-sensitive adhesive, and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of polarizer manufacturing, and in particular to a method for testing the aging process of a pressure-sensitive adhesive. Background Art

[0002] Pressure-sensitive adhesive (PSA adhesive for short) is a type of adhesive that is sensitive to pressure. According to the main components, pressure-sensitive adhesive can be divided into two types: rubber type and resin type. The resin type mainly includes acrylic, silicone and polyurethane. In the composition structure of polarizers, PSA adhesive is one of the core materials for manufacturing polarizers. For example, in a display panel, the role of PSA adhesive is to fit the polarizer to the liquid crystal box. At present, PSA adhesive for polarizers is usually acrylic, that is, it is composed of copolymers obtained by copolymerization of various acrylate monomers.

[0003] In the actual manufacturing process, after coating and drying to form a film (pre-curing), the solvent of the PSA glue is completely precipitated to form a PSA glue film. However, since the cross-linking reaction in the PSA glue has not been completely carried out, there is still uncross-linked curing agent. At this time, the performance of the PSA glue is very unstable and requires further cross-linking and curing, that is, ripening. If the PSA glue film is not fully ripened (that is, the PSA glue film has not reached the ripening end point), the polarizer with incompletely ripened PSA glue is cut and processed, the incompletely ripened PSA glue will overflow and adhere to the polarizer, resulting in a large amount of residual glue on the polarizer. Furthermore, the cost of monitoring the ripening process of existing pressure-sensitive adhesives is relatively high.

[0004] Therefore, it is urgent to design a test method for the aging process of a pressure-sensitive adhesive to solve the above problems. Summary of the invention

[0005] The present application provides a method for testing the aging process of a pressure-sensitive adhesive, so as to solve the problem of high testing cost of the aging process of the existing pressure-sensitive adhesive.

[0006] To achieve the above object, on the one hand, the present application provides a method for testing the aging process of a pressure-sensitive adhesive, the testing method comprising the following steps:

[0007] Obtaining the gel fraction of the pressure-sensitive adhesive after different time intervals;

[0008] Judging whether the pressure-sensitive adhesive is matured according to the gel fraction; and

[0009] When the gel fractions obtained at least twice consecutively are within a preset deviation range, it is determined that the pressure-sensitive adhesive is matured.

[0010] Optionally, in some embodiments of the present application, the test method for testing the curing process of the pressure-sensitive adhesive of the polarizer includes the following steps:

[0011] Obtaining a composite layer to be tested, wherein the composite layer to be tested comprises a pressure-sensitive adhesive layer and two release layers, wherein the two release layers are respectively attached to opposite sides of the pressure-sensitive adhesive layer in a thickness direction;

[0012] Obtaining the gel fraction of the pressure-sensitive adhesive layer in the composite layer to be tested after different time intervals;

[0013] Judging whether the pressure-sensitive adhesive layer of the composite layer to be tested is ripened according to the gel fraction; and

[0014] When the gel fractions obtained at least twice consecutively are within a preset deviation range, it is determined that the pressure-sensitive adhesive layer in the composite layer to be tested is ripened.

[0015] Optionally, in some embodiments of the present application, the step of obtaining the composite layer to be tested specifically includes:

[0016] Preparing a pressure-sensitive adhesive solution;

[0017] Applying the pressure-sensitive adhesive solution on the first release layer, and drying the pressure-sensitive adhesive solution to obtain a pressure-sensitive adhesive layer, wherein the pressure-sensitive adhesive layer is attached to the first release layer; and

[0018] The second release layer is laminated on the side of the pressure-sensitive adhesive layer away from the first release layer to obtain the composite layer to be tested.

[0019] Optionally, in some embodiments of the present application, in the process of drying the pressure-sensitive adhesive solution, the drying temperature is 80° C. to 100° C., and the drying time is 1 min to 3 min.

[0020] Optionally, in some embodiments of the present application, in the composite layer to be tested, the thickness of the pressure-sensitive adhesive layer is 15 μm to 30 μm.

[0021] Optionally, in some embodiments of the present application, in the composite layer to be tested, the release forces of the two release layers and the pressure-sensitive adhesive layer are different.

[0022] Optionally, in some embodiments of the present application, the step of obtaining the gel fraction of the pressure-sensitive adhesive layer in the composite layer to be tested at different time intervals includes:

[0023] In different time periods calculated from the completion of the step of obtaining the composite layer to be tested, portions of the composite layer to be tested are respectively cut out as the tested portions, and the gel fraction of the pressure-sensitive adhesive layer in the tested portions is obtained.

[0024] Optionally, in some embodiments of the present application, in the step of continuously acquiring the gel fraction of the pressure-sensitive adhesive layer in the composite layer to be tested, the process of testing the gel fraction of the pressure-sensitive adhesive layer includes the following steps:

[0025] Cut a portion of the composite layer to be tested as the portion to be tested, remove the two release layers of the portion to be tested and retain the pressure-sensitive adhesive layer thereof as a test sample, and obtain the weight M of the test sample;

[0026] The sample to be tested is configured as a sample solution to be tested; and,

[0027] Filtering the insoluble part of the sample solution to be tested, drying the insoluble part, and then obtaining the weight N of the insoluble part;

[0028] The gel fraction of the test sample was calculated according to the following formula: gel fraction = N / M*100%.

[0029] Optionally, in some embodiments of the present application, in the step of configuring the sample to be tested into a sample solution to be tested, ethyl acetate is used as a solvent for dissolving the sample to be tested.

[0030] Optionally, in some embodiments of the present application, in the step of drying the insoluble portion, the drying treatment temperature is 95° C. to 105° C., and the drying treatment time is 2 hours.

[0031] Compared with the prior art, the test method for the aging process of the pressure-sensitive adhesive of the present application continuously obtains the gel fraction of the pressure-sensitive adhesive after different time intervals, and determines whether the pressure-sensitive adhesive is aged according to the gel fraction. When the gel fractions obtained at least twice adjacently are within a preset deviation range, it is determined that the pressure-sensitive adhesive is aged, so as to solve the problem of high testing cost of the aging process of the pressure-sensitive adhesive. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For those skilled in the art, other drawings can be obtained based on these drawings without creative work.

[0033] Figure 1 Schematic diagram of the process of testing the aging process of a pressure-sensitive adhesive according to a first embodiment of the present application.

[0034] Figure 2 Schematic diagram of the flow chart of the second embodiment of the method for testing the aging process of a pressure-sensitive adhesive provided in an embodiment of the present application.

[0035] Figure 3 Schematic diagram of a composite layer to be tested provided according to an embodiment of the present application.

[0036] Figure 4A graph showing the relationship between the gel fraction of a pressure-sensitive adhesive provided in an embodiment of the present application and time, wherein the pressure-sensitive adhesive is used in a polarizer. DETAILED DESCRIPTION

[0037] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present application.

[0038] In the description of the present application, it should be understood that the terms "center", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", etc., indicating orientations or positional relationships, are based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present application and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as a limitation on the present application.

[0039] The terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Thus, a feature defined as "first" or "second" may explicitly or implicitly include one or more of the features. In the description of this application, unless otherwise specified, "plurality" means two or more.

[0040] In the description of this application, it should be noted that, unless otherwise clearly specified and limited, the terms "installed", "connected", and "connected" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection, a direct connection, or an indirect connection through an intermediate medium, or it can be the internal communication of two components. For ordinary technicians in this field, the specific meanings of the above terms in this application can be understood according to specific circumstances.

[0041] In order to better understand the solution of the present application, before describing the present application, some terms used in the description of the present application need to be briefly explained. "Gel fraction" refers to the mass fraction of gel in the cross-linked product. Gel fraction is a physical quantity that characterizes the degree of cross-linking of polymers.

[0042] Figure 1 FIG. 1 is a flow chart of a first embodiment of a method for testing the aging process of a pressure-sensitive adhesive according to an embodiment of the present application. Figure 1As shown, the present application provides a method for testing the aging process of a pressure-sensitive adhesive, the testing method comprising the following steps: obtaining the gel fraction of the pressure-sensitive adhesive after different time intervals; judging whether the pressure-sensitive adhesive is aged according to the gel fraction; and determining that the pressure-sensitive adhesive is aged when the gel fractions obtained at least twice consecutively are within a preset deviation range.

[0043] Compared with the prior art, the present invention determines the aging endpoint of the pressure-sensitive adhesive by testing the gel fraction of the pressure-sensitive adhesive after different time intervals, and then obtains the aging time of the pressure-sensitive adhesive and the gel fraction of the pressure-sensitive adhesive at its aging endpoint. The method for monitoring the gel fraction of the pressure-sensitive adhesive in the present invention is simple, highly operable, and low-cost, and can solve the problem of high testing cost during the aging process of the pressure-sensitive adhesive.

[0044] Furthermore, the aging time of the pressure-sensitive adhesive is used to guide the post-processing of the polarizer; and the component ratio of the pressure-sensitive adhesive in the polarizer can also be adjusted by the gel fraction of the pressure-sensitive adhesive at the end of aging. For example, in general, the higher the gel fraction, the harder the pressure-sensitive adhesive material is and the worse its fluidity is; the lower the gel fraction, the softer the pressure-sensitive adhesive material is and the stronger its fluidity is. In the production process of polarizers, the test method of the present application can be used to adjust the curing agent content of the pressure-sensitive adhesive in the polarizer to adjust the relative hardness and softness of the pressure-sensitive adhesive.

[0045] In specific implementation, the test method described in this application can be used to test the performance of a pressure-sensitive adhesive of a planned formula in a polarizer. Based on this, in order to improve the test accuracy of the aging process of the pressure-sensitive adhesive in the polarizer, the embodiment of this application specifically provides a second embodiment of the test method for the aging process of the pressure-sensitive adhesive for the polarizer. Figure 2 The test method for the aging process of the pressure-sensitive adhesive for polarizer shown in the figure specifically introduces the test method described in this application.

[0046] like Figure 2 As shown, in this embodiment, the testing method includes the following steps:

[0047] S100, obtaining a composite layer to be tested, wherein the composite layer to be tested comprises a pressure-sensitive adhesive layer and two release layers, wherein the two release layers are respectively attached to opposite sides of the pressure-sensitive adhesive layer in a thickness direction;

[0048] S200, obtaining the gel fraction of the pressure-sensitive adhesive layer in the composite layer to be tested after different time intervals;

[0049] S300, judging whether the pressure-sensitive adhesive layer of the composite layer to be tested is ripened according to the gel fraction; and

[0050] S400: When the gel fractions obtained at least twice consecutively are within a preset deviation range, determine that the pressure-sensitive adhesive layer in the composite layer to be tested is ripened.

[0051] In the solution of the present application, the pressure-sensitive adhesive to be tested is configured as the composite layer to be tested. In other words, the composite layer to be tested 100 formed by the pressure-sensitive adhesive to be tested is prepared. Figure 3 As shown, the composite layer 100 to be tested includes the pressure-sensitive adhesive layer 10 and two release layers in the thickness direction. The two release layers are a first release layer 20 and a second release layer 30, and the first release layer 20 and the second release layer 30 are respectively attached to both sides of the pressure-sensitive adhesive layer 10 in the thickness direction.

[0052] In the scheme of the present application, by configuring the pressure-sensitive adhesive to be tested as the composite layer 100 to be tested, on the one hand, the film morphology of the pressure-sensitive adhesive in the polarizer and the restoration simulation of the aging environment are achieved, so as to ensure that the gel fraction and aging time of the pressure-sensitive adhesive layer in the polarizer are accurately obtained, thereby more accurately guiding the polarizer process and the pressure-sensitive adhesive formula adjustment; on the other hand, during the test process, the two release layers in the composite layer 100 to be tested can also prevent the pressure-sensitive adhesive layer 10 from absorbing moisture and dust in the environment, thereby improving the accuracy and precision of each gel fraction test result.

[0053] Illustratively, the step of obtaining the composite layer 100 to be tested specifically includes:

[0054] S110, preparing a pressure-sensitive adhesive solution;

[0055] S120, coating the pressure-sensitive adhesive solution on the first release layer 20, and drying the pressure-sensitive adhesive solution to obtain a pressure-sensitive adhesive layer 10, wherein the pressure-sensitive adhesive layer 10 is attached to the first release layer 20; and

[0056] S130 , laminating the second release layer 30 on the side of the pressure-sensitive adhesive layer 10 away from the first release layer 20 to obtain the composite layer 100 .

[0057] In step S110, the pressure-sensitive adhesive solution can be configured according to the component formula of the pressure-sensitive adhesive to be tested. In specific implementation, the components of the pressure-sensitive adhesive can be directly mixed into a solvent according to the planned formula of the pressure-sensitive adhesive, and stirred evenly to form the pressure-sensitive adhesive solution. In schematic form, the curing agent and the binder constituting the pressure-sensitive adhesive can be directly added to ethyl acetate according to their respective component ratios, and stirred evenly to obtain the pressure-sensitive adhesive solution.

[0058] In the step S120, the pressure sensitive adhesive solution may be applied by spraying, spin coating or printing. Preferably, the pressure sensitive adhesive solution is applied by spin coating.

[0059] The process of "drying the pressure-sensitive adhesive solution" is essentially a process of volatilizing the solvent of the pressure-sensitive adhesive solution coated on the first release layer 20. Schematically, the drying temperature of the pressure-sensitive adhesive solution is 80°C to 100°C, and the drying time of the pressure-sensitive adhesive solution is 1min to 3min. By limiting the drying temperature and drying time, it is ensured that the solvent in the pressure-sensitive adhesive solution is completely volatilized.

[0060] In the specific implementation, the pressure-sensitive adhesive solution is dried in a drying oven. The drying temperature of the drying oven is set to 80° C., 85° C., 90° C., 95° C. or 100° C. The drying time of the drying oven is set to 1 min, 2 min or 3 min.

[0061] Specifically, according to the shrinkage ratio of the pressure-sensitive adhesive solution, the spraying amount of the pressure-sensitive adhesive solution is controlled so that the dry coating thickness of the pressure-sensitive adhesive is 15 to 30 μm. That is, in the composite layer 100 to be tested, the thickness of the pressure-sensitive adhesive layer 10 is 15 to 30 μm. The above thickness setting can make the film thickness of the pressure-sensitive adhesive layer 10 conform to the actual use scenarios such as polarizers and display panels, so that the test results can more accurately reflect the actual test parameters of the pressure-sensitive adhesive layer in the polarizer.

[0062] In a specific implementation, the thickness of the pressure-sensitive adhesive layer 10 is 15 μm, 20 μm, 22 μm, 25 μm, 28 μm or 30 μm. It should be noted that the specific implementation of the thickness of the pressure-sensitive adhesive layer 10 described in the present application is not limited thereto. In some embodiments not shown in the present application, the thickness of the pressure-sensitive adhesive layer 10 can be specifically set according to the actual requirements of the polarizer or display panel.

[0063] In the step S130, i.e., in the step of laminating the second release layer 30 to the side of the pressure-sensitive adhesive layer 10 away from the first release layer 20, the bonding is performed by utilizing the adhesive properties of the pressure-sensitive adhesive layer 10 itself, so that the lamination and transfer of the second release layer 30 does not require any temperature, is easy to operate, has the advantages of high applicability, low cost and high production efficiency, and can reduce the cost of the entire testing process.

[0064] Specifically, in order to ensure that the complete pressure-sensitive adhesive layer 10 can be taken out during the gel fraction test, the release forces between the two release layers and the pressure-sensitive adhesive layer 10 are different. Specifically in this embodiment, the release force between the first release layer 20 and the pressure-sensitive adhesive layer 10 is different from the release force between the second release layer 30 and the pressure-sensitive adhesive layer 10.

[0065] Schematically, the release force between the first release layer 20 and the pressure-sensitive adhesive layer 10 is greater than the release force between the second release layer 30 and the pressure-sensitive adhesive layer 10. At this time, the second release layer 30 can be torn off first, and then the first release layer 20 can be torn off to remove the complete pressure-sensitive adhesive layer from the test sample (see below for details).

[0066] In a specific implementation, the material of the first release layer 20 and the second release layer 30 can be, but is not limited to, PET. Schematically, the oily color layer PET-703 series, PET-820 series, or water-based color layer PET-7030 series coatings of Bang Curing Science can be used. In a specific implementation, in order to make the release forces of the two release layers different, the materials of the two release layers are different.

[0067] In the step S200, at different time periods calculated from the completion of the step of obtaining the composite layer 100 to be tested, portions of the composite layer 100 to be tested are respectively cut out as the tested portion, and the gel fraction of the pressure-sensitive adhesive layer in the tested portion is obtained. It can be understood that the gel fraction of the pressure-sensitive adhesive layer in the tested portion is substantially the gel fraction of the pressure-sensitive adhesive layer 10 of the composite layer 100 to be tested.

[0068] Indicative, Figure 4 A graph showing the relationship between the gel fraction of a pressure-sensitive adhesive and time is provided, wherein the pressure-sensitive adhesive is used in a polarizing film. Figure 4 As shown, P1~P 15 The 15 test points respectively represent the gel fraction of the pressure-sensitive adhesive layer 10 of the composite layer 100 to be tested obtained from the time of 1 day to 15 days from the completion of the preparation step of obtaining the composite layer 100 to be tested. n represents the gel fraction of the pressure-sensitive adhesive layer 10 of the composite layer 100 to be tested n days after the composite layer 100 to be tested is obtained, wherein n is a positive integer ranging from 1 to 15. Schematically, P1 represents the gel fraction of the pressure-sensitive adhesive layer 10 of the composite layer 100 to be tested 1 day after the composite layer 100 to be tested is obtained. 15 P5 represents the gel fraction of the pressure-sensitive adhesive layer 10 of the composite layer 100 to be tested 15 days after the composite layer 100 to be tested is obtained. P6 represents the gel fraction of the pressure-sensitive adhesive layer 10 of the composite layer 100 to be tested 5 days after the composite layer 100 to be tested is obtained.

[0069] In the step of continuously obtaining the gel fraction of the pressure-sensitive adhesive layer in the composite layer to be tested, the process of testing the gel fraction of the pressure-sensitive adhesive includes the following steps:

[0070] (1) cutting a portion of the composite layer to be tested as the portion to be tested, removing the two release layers of the portion to be tested and retaining the pressure-sensitive adhesive layer thereof as a test sample, and obtaining a weight M of the test sample;

[0071] (2) preparing the sample to be tested into a sample solution;

[0072] (3) filtering the insoluble portion of the sample solution to be tested, drying the insoluble portion, and then obtaining the weight N of the insoluble portion; and,

[0073] (4) Calculate the gel fraction of the test sample according to the following formula: Gel fraction = N / M*100%.

[0074] Specifically in this embodiment, the gel fraction can be understood as the weight ratio of the insoluble part (or residual glue) in the sample solution to be tested.

[0075] In the step (1), a portion to be tested with a size of 5 cm*5 cm is cut from the composite layer to be tested, and the portion to be tested is weighed with an analytical balance, and the weight of the portion to be tested is recorded as A. Further, the two release layers of the portion to be tested are removed and the pressure-sensitive adhesive layer of the portion to be tested is retained and taken out as a test sample, and the weight of the two release layers is weighed with an analytical balance, and the weight of the two release layers is recorded as B. At this time, the weight of the test sample M=AB.

[0076] In the step (2), i.e., the process of configuring the sample to be tested into a sample solution to be tested is specifically as follows: using tweezers to take out the pressure-sensitive adhesive layer of the part to be tested (i.e., the test sample), and placing the test sample in a sealed transparent container (e.g., a conical flask), adding 5g of ethyl acetate to soak, and placing for a period of time to obtain the sample solution to be tested. In specific implementation, the placement time and placement environment can be adjusted according to the dissolution of the test sample. Schematically, the sealed transparent container containing ethyl acetate and the test sample is placed in an environment with a temperature of 21-23°C and a humidity of 55%RH-65%RH for 48 hours.

[0077] Specifically in this embodiment, the gel fraction can be understood as the weight ratio of the ethyl acetate insoluble part (or residual adhesive) in the pressure-sensitive adhesive layer.

[0078] In step (3), the sample solution to be tested can be filtered using a metal mesh with a weight of C, at which point the insoluble portion of the sample solution to be tested is completely attached to the metal mesh; the filtered metal mesh (i.e., the metal mesh with the insoluble portion attached) is dried, and the weight D of the metal mesh is obtained again. At this point, the weight N of the insoluble portion = DC.

[0079] In the specific implementation, the metal mesh is selected from a 200 mesh metal mesh. The metal mesh is cut into squares with a specification of 10 cm*10 cm. In the actual test, the metal mesh can be soaked in ethyl acetate for 10 hours to remove organic impurities adhering to the metal mesh, and then taken out and dried for later use.

[0080] In the process of drying the insoluble part, the drying temperature is 95°C to 105°C, and the drying time is 2 hours. In the specific implementation, the insoluble part is dried in a drying oven, and the drying temperature of the drying oven is set to 95°C, 100°C or 105°C.

[0081] The above schematically shows the implementation of filtering and weighing the insoluble part using a metal mesh. However, it should be noted that the present application does not limit the method of filtering and weighing the insoluble part. In other embodiments, the sample solution to be tested can also be filtered using gauze, and the filtered filter cloth and the insoluble part (residual glue) are placed in a 150°C oven for 1 hour, and then taken out for weighing and calculation.

[0082] In the steps S300 to S400, whether the pressure-sensitive adhesive layer of the composite layer to be tested is matured is determined according to the gel fraction; when the gel fractions obtained at least twice in a row are within a preset deviation range, it is determined that the pressure-sensitive adhesive layer in the composite layer to be tested is matured. The preset deviation range can be specifically adjusted during the test process.

[0083] It is understandable that as the time interval increases, the change in the degree of maturation of the pressure-sensitive adhesive gradually decreases, which means that the change in the gel fraction of the pressure-sensitive adhesive will also remain in a small range. For details, please refer to Figure 4 When the difference between the gel fractions measured twice or more times is within the preset deviation range, the degree of maturation of the pressure-sensitive adhesive layer is relatively close to the maturation endpoint. When the gel fractions measured for multiple consecutive times tend to be consistent, the pressure-sensitive adhesive is fully maturated, or the pressure-sensitive adhesive reaches the maturation endpoint.

[0084] In the description of this specification, specific features, structures, materials or characteristics may be combined in an appropriate manner in any one or more embodiments or examples.

[0085] The above is only a specific implementation of the present application, but the protection scope of the present application is not limited thereto. Any technician familiar with the technical field can easily think of changes or substitutions within the technical scope disclosed in the present application, which should be included in the protection scope of the present application. Therefore, the protection scope of the present application shall be based on the protection scope of the claims. In addition, the specification uses specific examples to illustrate the principles and implementation methods of the present application. The description of the above embodiments is only used to help understand the method and its core idea of ​​the present application. The content of this specification should not be understood as a limitation on the present application.

Claims

1. A method for testing the aging process of a pressure-sensitive adhesive, characterized in that: The test method for the curing process of the pressure-sensitive adhesive of the polarizer comprises the following steps: Obtaining a composite layer to be tested, wherein the composite layer to be tested comprises a pressure-sensitive adhesive layer and two release layers, wherein the two release layers are respectively attached to opposite sides of the pressure-sensitive adhesive layer in a thickness direction; Obtaining the gel fraction of the pressure-sensitive adhesive layer in the composite layer to be tested after different time intervals; Judging whether the pressure-sensitive adhesive layer of the composite layer to be tested is ripened according to the gel fraction; and When the gel fractions obtained at least twice consecutively are within a preset deviation range, it is determined that the pressure-sensitive adhesive layer in the composite layer to be tested is ripened.

2. The method for testing the aging process of a pressure-sensitive adhesive as claimed in claim 1, characterized in that: The step of obtaining the composite layer to be tested specifically includes: Preparing a pressure-sensitive adhesive solution; Applying the pressure-sensitive adhesive solution on the first release layer, and drying the pressure-sensitive adhesive solution to obtain a pressure-sensitive adhesive layer, wherein the pressure-sensitive adhesive layer is attached to the first release layer; and The second release layer is laminated on the side of the pressure-sensitive adhesive layer away from the first release layer to obtain the composite layer to be tested.

3. The method for testing the aging process of a pressure-sensitive adhesive as claimed in claim 2, characterized in that: In the process of drying the pressure-sensitive adhesive solution, the drying temperature is 80° C. to 100° C., and the drying time is 1 min to 3 min.

4. The method for testing the aging process of a pressure-sensitive adhesive according to claim 1, wherein: In the composite layer to be tested, the thickness of the pressure-sensitive adhesive layer is 15 μm to 30 μm.

5. The method for testing the aging process of a pressure-sensitive adhesive as claimed in claim 1, characterized in that: In the composite layer to be tested, the release forces of the two release layers and the pressure-sensitive adhesive layer are different.

6. The method for testing the aging process of a pressure-sensitive adhesive as claimed in claim 1, characterized in that: The step of obtaining the gel fraction of the pressure-sensitive adhesive layer in the composite layer to be tested at different time intervals comprises: In different time periods calculated from the completion of the step of obtaining the composite layer to be tested, portions of the composite layer to be tested are respectively cut out as the tested portions, and the gel fraction of the pressure-sensitive adhesive layer in the tested portions is obtained.

7. The method for testing the aging process of a pressure-sensitive adhesive according to claim 1, characterized in that: In the step of obtaining the gel fraction of the pressure-sensitive adhesive layer in the composite layer to be tested after different time intervals, the process of testing the gel fraction of the pressure-sensitive adhesive layer includes the following steps: Cut a portion of the composite layer to be tested as the portion to be tested, remove the two release layers of the portion to be tested and retain the pressure-sensitive adhesive layer thereof as a test sample, and obtain the weight M of the test sample; The sample to be tested is configured as a sample solution to be tested; and, Filtering the insoluble part of the sample solution to be tested, drying the insoluble part, and then obtaining the weight N of the insoluble part; The gel fraction of the test sample was calculated according to the following formula: Gel fraction = N / M 100%.

8. The method for testing the aging process of a pressure-sensitive adhesive as claimed in claim 7, characterized in that: In the step of configuring the sample to be tested into a sample solution, ethyl acetate is used as a solvent for dissolving the sample to be tested.

9. The method for testing the aging process of a pressure-sensitive adhesive as claimed in claim 7, characterized in that: In the step of drying the insoluble part, the drying temperature is 95° C. to 105° C., and the drying time is 2 hours.

Citation Information

Patent Citations

  • Pressure-sensitive adhesive and surface-protecting pressure-sensitive adhesive sheet made with the same

    WO2009037990A1